KAJIAN KOMPARATIF KUALITAS SIFAT FISIK TANAH PADA SISTEM PENGELOLAAN PERKEBUNAN KELAPA SAWIT RAKYAT DAN PERKEBUNAN BESAR SWASTA - Wianita , Dyah Ayu; Ajidirman, Ajidirman; Saad, Asmadi; Wiskandar, Wiskandar (Jurnal Agroecotania : Publikasi Nasional Ilmu Budidaya Pertanian, 2026)
Smallholder oil palm plantations generally do not apply organic fertilizer management systems or soil conservation techniques, whereas large private plantations (PT. MSP) apply organic fertilizers in the form of empty fruit bunches and implement soil conservation practices. Differences in land management between smallholder plantations and large-scale oil palm companies influence the physical properties of the soil. This study was conducted to compare the quality of soil physical properties in oil palm plantation areas of smallholder plantations and large private plantations (PT. MSP) in Bungo Regency, Jambi Province. The study employed a Systematic Grid Survey method, in which undisturbed and disturbed soil samples were collected at a depth of 0–30 cm within several Homogeneous Land Units (HLUs). The soil samples were subsequently analyzed for soil texture, bulk density, total pore space, moisture content, aggregate stability, and organic matter content. The resulting data were used to calculate the Soil Physical Quality Index (SPQI) as an indicator of soil physical quality. The results indicated that soil quality in the PT. Mega Sawindo Perkasa plantation was classified as ‘moderate,’ with an average SPQI value ranging from 0.59 to 0.69. In contrast, the smallholder plantations were categorized as ‘fairly poor,’ with an average SPQI value ranging from 0.50 to 0.56. To improve soil quality, it is recommended that smallholder plantations apply organic fertilizers and implement terracing practices to reduce erosion and enhance soil structure.